تحليل نقدي للخطاب حول تمثيل النوع الاجتماعي في كتب اللغة الإنجليزية كلغة أجنبية في ليبيا - Al Hajaji, Afaf Hussien (Al-Qurtas, 2025)
تحليل نقدي للخطاب حول تمثيل النوع الاجتماعي في كتب اللغة الإنجليزية كلغة أجنبية في ليبيا